Peran sanro bola dalam tradisi membangun rumah tradisional Bugis di Kabupaten Soppeng - Asta Juliarman Hatta; Iwan Sudradjat (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2020)
The role of sanro bola in construction of Bugis traditional house in Soppeng District The diversity of race and culture makes Indonesia a country with abundance of culture. Traditional houses which have diverse form are symbol and reflection of culture in every tribe in Indonesia. The shape and architectural value of traditional Bugis houses in Sulawesi Selatan which still remains thanks to the efforts of Bugis tribe community is an example of house-building culture which still exists today. The involvement of cultural leader such as Sanro bola in tradition of Bugis’ house-building culture is essential, because they have knowledge and experiences passed on through generations. This study aims to reveal the role of Sanro bola in preserving the traditional values of building a Bugis Soppeng house. The method of this research is qualitative with explorative analysis. The result of the study revealed that the role of Sanro bola in the process of building a traditional Bugis Soppeng house divided into 6 aspects; as leader, material selection, considering about a good time and day, house orientation, constructing of traditional houses, and application of philosophy sulapa epapa'e. These six aspects are applied by Sanro bola in both physical and non-physical with the aim of providing direction and safety for the residents of the house.